The effect of Foreign Body Aspiration training on the knowledge level of pupils - Akca,Selen Ozakar (2016)
ABSTRACT INTRODUCTION: Educators dealing with 0-6 years old children must be individuals who are willing to take all kind of measures in order to ensure the safety of children in educational institutions and playgrounds, providing protection from diseases, and who are able to apply first aid measures in case of an accident. OBJECTIVE: In this study, we aimed to determine the level of knowledge of all students continuing their education in the department for child development, regarding Foreign Body Aspiration (FBA) and the effect of FBA training on their knowledge level. METHODS: This semi-experimental study was carried out on high-school students (n = 123) continuing their education in the department for child development in Corum, Turkey. The data was evaluated with appropriate statistical methods, and p < 0.05 was determined as statistically significant. RESULTS: Before the training, 80% of the high-school children knew the importance of age factor in cases of FBA, improving to 92% after training. The increase in the number of students who were aware of the importance of age factor was statistically significant (p < 0.05). CONCLUSION: As a result of the training, the visual presentation and training on models related to FBA have led to an increase in the knowledge level of the students.